2021
DOI: 10.1002/aac2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and fitness in childhood cancer survivors: A scoping review

Abstract: Background: Estimates indicate that nearly 8% of the over 500,000 survivors of childhood cancer living in the United States are frail in their fourth and fifth decades of life, a phenotype typically seen in geriatric populations. Participation in regular physical activity to improve physical fitness in healthy and diseased populations reduces risk for frail health by increasing physiologic reserve. However, physical activity may not have the same effects on fitness in childhood cancer survivors as it does amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 110 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…[14][15][16] PA is especially important for young cancer survivors, as PA can reduce their risk of late effects such as metabolic syndrome, cardiovascular disease, and premature death. [17][18][19][20][21] Regardless, most survivors are less active than siblings and age-matched healthy controls. [22][23][24] A recent study found that only 25% of childhood cancer survivors meet PA recommended guidelines (60 minutes a day).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] PA is especially important for young cancer survivors, as PA can reduce their risk of late effects such as metabolic syndrome, cardiovascular disease, and premature death. [17][18][19][20][21] Regardless, most survivors are less active than siblings and age-matched healthy controls. [22][23][24] A recent study found that only 25% of childhood cancer survivors meet PA recommended guidelines (60 minutes a day).…”
Section: Introductionmentioning
confidence: 99%
“…Participating in physical activity (PA) in childhood is essential for attaining developmental milestones, improving physical fitness, and forming long‐lasting beneficial lifestyle behaviors 14–16 . PA is especially important for young cancer survivors, as PA can reduce their risk of late effects such as metabolic syndrome, cardiovascular disease, and premature death 17–21 . Regardless, most survivors are less active than siblings and age‐matched healthy controls 22–24 .…”
Section: Introductionmentioning
confidence: 99%
“…6,39 We recommend identifying survivors at risk for cardiovascular disease early and offering support with targeted interventions. 40,41 Physical activity has been shown as beneficial and safe during and after treatment, 42,43 yet currently well below recommended levels. [44][45][46][47] Some children need special support because of musculoskeletal or medical impairments.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review on the topic could provide important information about the breadth of evidence available, offer guidance for future exercise interventions designed to prevent cardiotoxicity in CACS, and identify where more research is necessary. While several reviews are available, none have explored the impact of exercise interventions on heart health in CACS (Huang & Ness, 2011;Upshaw, 2020;Varghese et al, 2021;Wogksch et al, 2021;Wurz, McLaughlin, Lategan, Ellis, & Culos-Reed, 2021).…”
Section: Introductionmentioning
confidence: 99%